2009
DOI: 10.1021/la9007608
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Adsorbed Polyelectrolyte Monolayer on Oppositely Charged Colloidal Particles

Abstract: An adsorbed layer of a cationic polyelectrolyte, poly(diallyldimethyl-ammonium) chloride (PDADMAC) on negatively charged colloidal latex particles was investigated by small-angle neutron scattering (SANS) and dynamic light scattering (DLS). SANS gives a layer thickness of 8 +/- 1 A and a polymer volume fraction of 0.31 +/- 0.05 within the film. DLS gives a somewhat larger thickness of 18 +/- 2 A, and the discrepancy is likely due to the inhomogeneous nature of the layer and the existence of polymer tails or lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…68 Figure 7 shows that X w decreases from values close to 1 for low number of layers until a quasiplateau value (N ∼ 10); this qualitative behavior is independent of the system studied in the present work, which suggests that the polymer chains adsorb rather inhomogeneously in the first layers forming isolated adsorbed pancake. [69][70][71] These results are in accordance with the model previously reported by us for multilayers of (PDADMAC þ PSS) n 34 and with the structural results obtained by AFM of multilayers by Kujawa et al 72 The very high content found for the first adsorbed layer is also in qualitative agreement with the results of Vaccaro et al 69 Figure 8 shows X w for multilayers with 20 layers for all the multilayers studied in this work. It is observed that the water content depends on the copolymers and on the concentration of copolymer.…”
Section: Discussionsupporting
confidence: 92%
“…68 Figure 7 shows that X w decreases from values close to 1 for low number of layers until a quasiplateau value (N ∼ 10); this qualitative behavior is independent of the system studied in the present work, which suggests that the polymer chains adsorb rather inhomogeneously in the first layers forming isolated adsorbed pancake. [69][70][71] These results are in accordance with the model previously reported by us for multilayers of (PDADMAC þ PSS) n 34 and with the structural results obtained by AFM of multilayers by Kujawa et al 72 The very high content found for the first adsorbed layer is also in qualitative agreement with the results of Vaccaro et al 69 Figure 8 shows X w for multilayers with 20 layers for all the multilayers studied in this work. It is observed that the water content depends on the copolymers and on the concentration of copolymer.…”
Section: Discussionsupporting
confidence: 92%
“…From the adsorbed amount and the layer thickness at the ASP, one can estimate the average volume fraction of the polyelectrolyte within the film to be between 10% and 20%. Comparable volume fractions were found for PDADMAC in a very similar system by small angle neutron scattering [19]. While one might be tempted to suspect a strongly swollen film, we rather believe that the adsorbed film is laterally heterogeneous and probably consists of compact patches of the adsorbed polyelectrolyte and partially void surface.…”
Section: Layer Thicknesssupporting
confidence: 50%
“…As a consequence, any polyelectrolyte that is further added remains dissolved in solution, while below the ASP the adsorption of the polyelectrolyte is quantitative. The resulting polyelectrolyte layers are thin and laterally heterogeneous [11,14,19,20]. However, their structure remains a subject of research, and will also be discussed here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle neutron scattering experiments have been successfully used to study this property (Mears et al, 1998;Hone et al, 2002;Oberdisse, 2007;Vaccaro et al, 2009). This technique has the advantage that simultaneous measurements of the adsorbed amount and of the layer thickness are possible.…”
Section: Structure Of Adsorbed Polymer Layersmentioning
confidence: 99%